MONITORING SLEEP AND HEART RATE IN CHILDREN: ASSESSMENT BASED ON DIGITAL TECHNOLOGIES - Sanjarbek Ataxanov Anvarovich; Ozodbek Azimjonov Muhiddin o'g'li; Abdulkhamidov Azizjon Abdullaugli (Bright Mind Publishing, 2025)
Assessing sleep quality and heart rate in children is considered essential for maintaining their health. Thanks to digital technologies, it has become possible to identify and analyze these indicators in real time. This article explores how smart devices, biosensors, mobile applications, and artificial intelligence algorithms can be used to monitor sleep and heart rhythm in children. It highlights the advantages of these technologies and presents findings from practical studies. The clinical significance of the monitoring results and future perspectives are also discussed.
Keywords: sleep monitoring, heart rate, children's health, digital healthcare, smart devices, artificial intelligence, wearable technologies